Biological relevance of volatile organic compounds emitted during the pathogenic interactions between apple plants and Erwinia amylovora. (13th January 2017) - Cellini, Antonio; Buriani, Giampaolo; Rocchi, Lorenzo; Rondelli, Elena; Savioli, Stefano; Rodriguez Estrada, Maria T.; Cristescu, Simona M.; Costa, Guglielmo; Spinelli, Francesco
Summary: Volatile organic compounds emitted during the infection of apple ( Malus pumila var. domestica ) plants by Erwinia amylovora or Pseudomonas syringae pv. syringae were studied by gas chromatography‐mass spectrometry and proton transfer reaction‐mass spectrometry, and used to treat uninfected plants. Infected plants showed a disease‐specific emission of volatile organic compounds, including several bio‐active compounds, such as hexenal isomers and 2, 3‐butanediol. Leaf growth promotion and a higher resistance to the pathogen, expressed as a lower bacterial growth and migration in plant tissues, were detected in plants exposed to volatile compounds from E. amylovora ‐infected plants. Transcriptional analysis revealed the activation of salicylic acid synthesis and signal transduction in healthy plants exposed to volatiles produced by E. amylovora ‐infected neighbour plants. In contrast, in the same plants, salicylic acid‐dependent responses were repressed after infection, whereas oxylipin metabolism was activated. These results clarify some metabolic and ecological aspects of the pathogenic adaptation of E. amylovora to its host.